1975
DOI: 10.5703/1288284313894
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the 55 MPH Speed Limit

Abstract: Speed limits have been established for the good of the motoring public, primarily for purposes of safety. A study has shown that by reducing the number of violators on freeways, the resulting more uniform speeds contribute to improved capacity and safety (22). The effectiveness of a speed limit on a facility depends on the degree of enforcement and public support (3,4). The public will support and obey speed limits that are safe and reasonable; however, speed limits that are illogically restrictive cannot be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Additionally, the entire speed distribution is examined along with variabilities in speed instead of just the mean speed. Several studies utilize aggregate data to compare before-after speed metrics using ordinary least squares (OLS) regression techniques (5,34,35,40,41) and others use analysis of variance (ANOVA) and t-tests (36,37,42). Testing only the mean speed (using linear regression or a typical t-test or ANOVA) cannot indicate whether the changes or differences observed are the result of slower traffic driving faster now, or faster traffic driving much faster, or both.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the entire speed distribution is examined along with variabilities in speed instead of just the mean speed. Several studies utilize aggregate data to compare before-after speed metrics using ordinary least squares (OLS) regression techniques (5,34,35,40,41) and others use analysis of variance (ANOVA) and t-tests (36,37,42). Testing only the mean speed (using linear regression or a typical t-test or ANOVA) cannot indicate whether the changes or differences observed are the result of slower traffic driving faster now, or faster traffic driving much faster, or both.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In response to the NMSL in 1974, several research studies were conducted to evaluate its effects. One 1975 study in Indiana saw fatalities on rural highways decrease by 67%, personal injury crashes decrease by 32%, and property damage only crashes decrease by 13% in the first half of 1974 when compared with the same period of the three previous years ( 1 ). Another study in Michigan over the same time period saw a 20% decrease in total crashes and injury crashes and a 17% decrease in fatal crashes on freeways ( 2 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Maximum statutory speed limits have been an issue of longstanding debate. Following the introduction of the National Maximum Speed Limit (NMSL) in 1974, a series of longitudinal studies showed significant decreases in traffic fatalities ( 1 , 2 ). In 1987, states were given the authority to increase limits on rural interstates to 65 mph, spurring a series of additional research studies that showed marked increases in fatalities subsequent to these speed limit increases ( 3 , 4 ).…”
mentioning
confidence: 99%